AN ANALYSIS OF STUDENTS’ ABILITY IN WRITING CAUSE AND EFFECT ESSAY AT SMAN 1 KEDIRI - Nurul Aini; Deny Ega Widayanti; Agus Edi Winarto (Journey: Journal of English Language and Pedagogy, 2022)
This study aims to find the ability, the problems as well as how they solve them in writing cause and effect essay. This research used descriptive qualitative. The data were obtained by analyzing the students’ essay writing based on Jacobs et al, assessing rubric instrument, calculating questionnaire from 32 respondents, and transcribing interview from the English teacher. The subject is the students of eleventh-grade SMAN 1 Kediri. The result showed that the ability of students in writing cause and effect classified as “Good” based on the means score of the students’ cause and effect essay. It was found twelve students had problem in language use, seven students had problem in mechanics, there were six students had problem in content, five students had problem in organization and two students had problem in vocabulary. Also, there were three kinds of solutions offered by the students such as using internet to access various source, using dictionary, and practice writing more.